Peran Guru dalam Meningkatkan Keaktifan Belajar Siswa pada Kegiatan Pembelajaran Daring Kelas V di SD Negeri 1 Purbalingga Wetan - Rosita Dwi Aprilia; Dhi Bramasta (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
The purpose of this study was to determine the teacher's role in student learning activities in online learning in class V SD Negeri 1 Purbalingga Wetan. This type of research is qualitative with fifth grade teachers, students, and parents as participants, data collection is done through interviews and documents. Data analysis was carried out through the process of data reduction, data presentation, drawing conclusions and verification using the Miles and Huberman model. Testing the validity of the data using source triangulation. The results showed that the active learning of students during online learning was quite good, this was because not all students did not really understand the material and tasks given by the teacher. Students still find it difficult when they find questions or materials that they feel are difficult or do not understand so they have to ask for help from their parents or relatives at home. In the implementation of online learning now students are given handbooks by the school in the form of modules or theme books to make it easier for students to learn and do the tasks given by the teacher, students must also have a handbook other than the one given by the school to make it easier for students to learn and look for other materials. required. The implementation of online learning in class V of SD Negeri 1 Purbalingga Wetan, of course, has several obstacles, namely the area where the student lives is sometimes still difficult to signal, so when the teacher sends assignments or provides material it can take quite a long time. Vice versa if the student will send it back. In addition, there are other obstacles, namely the difficulty of communication between teachers and parents of students. It is difficult to communicate with parents because they also have a number of other jobs to do, not only supervising their children while studying and the signal network constraints that make communication a bit hampered.